2009
DOI: 10.1080/00365590902834802
|View full text |Cite
|
Sign up to set email alerts
|

Open retropubic prostatectomy versus robot-assisted laparoscopic prostatectomy: A comparison of length of sick leave

Abstract: Objective. It remains uncertain whether the increased direct costs of robot-assisted laparoscopic radical prostatectomy (RALP) are outweighed by cost savings due to shorter postoperative hospital care and shorter sick leave. This study compared the length of sick leave after RALP with that after radical retropubic prostatectomy (RRP). Material and methods. In a cohort study, information on length of sick leave was retrieved for 274 working men undergoing radical prostatectomy (127 RALP and 147 RRP). Data on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 10 publications
7
22
0
Order By: Relevance
“…Blood loss was significantly lower in the RALP group on both univariate and multivariate analyses, which indicates that this method reduces the surgical trauma. This is in concordance with previous studies [4,7,16] and may contribute to the shorter duration of both in-hospital stay and postoperative sick leave for RALP-treated patients [16,18].…”
Section: Discussionsupporting
confidence: 93%
“…Blood loss was significantly lower in the RALP group on both univariate and multivariate analyses, which indicates that this method reduces the surgical trauma. This is in concordance with previous studies [4,7,16] and may contribute to the shorter duration of both in-hospital stay and postoperative sick leave for RALP-treated patients [16,18].…”
Section: Discussionsupporting
confidence: 93%
“…Supporters of robotic surgery often cite a reduced LOS as an advantage to the patient and means for cost-savings [5, 9, 2225]. In this study, the median LOS for RP and OP were equivalent.…”
Section: Discussionmentioning
confidence: 67%
“…A key proposed benefit of RALP is that, given the smaller incisions required, patients experience less pain, and ‘faster recovery and return to normal activities’ [14]. Indeed, randomized trials of ORP vs RALP have demonstrated that patients having RALP take less sick leave [25], and have a faster return to baseline quality of life [26]. There are, however inherent difficulties with blinding patients and health practitioners in such trials, and the possibility that that recovery might have been influenced by preconceived patient/practitioner expectations in those studies cannot be discounted.…”
Section: Discussionmentioning
confidence: 99%